Fast Delamination of Fuel Cell Catalyst-Coated Membranes Using High-Intensity Ultrasonication - Tanongsak Yingnakorn; Ross Gordon; Daniel Marin Florido; Christopher E. Elgar; Ben Jacobson; Shida Li; Paul Prentice; Andrew P. Abbott; Jake M. Yang (Ultrasonics Sonochemistry)
This study demonstrates a rapid and facile method for separating the central membrane and catalyst-coated material from production scrap fuel cell catalyst-coated membranes (CCMs), facilitating a circular economy of technologically critical metals. A novel approach is presented using high-intensity ultrasonication with two distinct sonotrode configurations for rapid delamination at ambient temperature in water. This technique utilises cavitation, where high-frequency sound waves create, expand, and collapse microbubbles, generating high-speed jets, shockwaves, and acoustic streaming. This process effectively separates the membrane and catalyst while maintaining their overall integrity of the former. A cylindrical sonotrode (20 mm diameter) was used to optimise process parameters for smaller CCM samples to minimise time and energy consumption. To scale up the delamination process for industrial-size CCMs, a blade sonotrode (15 mm x 210 mm) was employed to enable a flow process for rapid and continuous delamination. Cavitation at the sonotrode-CCM interface was shown to facilitate the selective and rapid breakdown of the catalyst layers, enabling full delamination of the catalyst-loaded membrane within tens of seconds. This efficient and fast delamination approach offers a promising strategy for CCM recycling.